Analyzing The Use of English for Tactical Communication Between Coaches and Athletes - Elisa Haddina; Arsi Zahiri; Faldin Sejahtera Halawa; Robert Parulian Marko Bancin; S. Ahmad Habibi; Muhammad Naufal Ramadhan; Deddy Putrawan Laia (Joska: Jurnal Isori Kampar, 2026)
Objectives: This research investigates the linguistic patterns, communicative effectiveness, and functional applications of English language use in tactical communication between coaches and athletes across multiple competitive sports. The study examines how English as a lingua franca facilitates strategic discourse, decision-making processes, and performance optimization in multilingual sporting environments. Methods: A mixed-methods approach was employed, involving 156 participants (78 coaches and 78 athletes) from 12 countries across six sports disciplines. Data collection included audio recordings of tactical communications (n=312 sessions), semi-structured interviews, linguistic corpus analysis, and validated questionnaires. Statistical analyses utilized ANOVA, regression modeling, and discourse analysis frameworks. Results: Analysis revealed that 73.4% of tactical communication utilized English regardless of participants' native languages. Key linguistic features included simplified syntax (M=8.3 words per utterance), specialized sports terminology (42.1% of lexical items), and imperative mood structures (61.8% of directives). Significant positive correlations emerged between English proficiency levels and tactical comprehension accuracy (r=0.74, p<0.001) and between communication clarity and performance outcomes (r=0.68, p<0.001). Conclusion: English functions as a critical medium for tactical communication in international sports contexts, demonstrating distinct linguistic characteristics optimized for rapid information transfer. The findings suggest that targeted English language training for tactical communication can significantly enhance coach-athlete interaction effectiveness and competitive performance. The study contributes theoretical insights into domain-specific language use and practical implications for sports pedagogy and athlete development programs.